The ApoE receptors Vldlr and Apoer2 in central nervous system function and disease - Lane-Donovan, Courtney (J Lipid Res, 2017)
The LDL receptor (LDLR) family has long been studied for its role in cholesterol transport and metabolism; however, the identification of ApoE4, an LDLR ligand, as a genetic risk factor for late-onset Alzheimer’s disease has focused attention on the role this receptor family plays in the CNS. Surprisingly, it was discovered that two LDLR family members, ApoE receptor 2 (Apoer2) and VLDL receptor (Vldlr), play key roles in brain development and adult synaptic plasticity, primarily by mediating Reelin signaling. This review focuses on Apoer2 and Vldlr signaling in the CNS and its role in human disease.